Determination of physical properties of siamese oranges (Citrus nobilis var. Microcarpa): sphericity, roundness, volume, and density - Kurniawati, Emi; Rakhmadevi, Ade Galuh; Fadhila, Putu Tessa; Lailah, Syarifatul (Journal of Agritechnology and Food Processing, 2023)
Siamese oranges are a member of the tangerines which have the scientific name Citrus nobilis var.Microcarpa. It is called Siamese orange because it comes from Siam (Muangthai). The quality of Siamese oranges is determined by their physical properties. These physical properties include size, weight, volume and diameter. Post-harvest technology for Siamese oranges can be done by grading to obtain quality Siamese oranges according to standards. This research aims to determine the physical properties of Siamese oranges used in the grading process. Determination of sphericity and roundness is measured using a caliper. Determination of volume and density is measured using a beaker. Analysis of research data used a one-way z-test normal distribution to the left. The results of data analysis show that the z-count value of roundness, roundness, volume and density is 1.05; 0.79; 0.55; 0.53 and -ztable of -1.645. This means zcount ≥ -ztable, where the average value of the physical properties of Siamese oranges is greater than or equal to the research object, roundness is 0.92, roundness is 0.93, volume is 87 cm3 and density is 1.02 g/ cm3. Thus, the results of these physical properties can be used as a reference when grading Siamese oranges code size 2.